STRATEGI GURU DALAM MENGINTEGRASIKAN NILAI KARAKTER KE DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Tri Rohana Wati; Haifaturrahmah; Sukron Fujiaturrahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe teachers’ strategies in integrating character values into Science and Social Studies (IPAS) learning in elementary schools. This research applies a qualitative descriptive approach with classroom teachers and students as the main participants. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results show that teachers apply various strategies to integrate character values, including modeling, habituation, contextual discussions, and project-based activities that foster environmental awareness and cooperation. IPAS learning not only focuses on cognitive understanding but also builds students’ social sensitivity, responsibility, and curiosity toward their surroundings. Despite several challenges, character integration in IPAS effectively shapes students to become knowledgeable, ethical, and socially responsible individuals. Keywords: Teacher Strategy, Character Values, IPAS Learning, Elementary School